User evaluation of Chinese studies collection in an academic library / Chia Yip Ping - Chia , Yip Ping (2008)
A user assessment study was conducted to evaluate the level of satisfaction of users with the Chinese studies collection and library services and facilities at the University of Malaya Library. The respondents are library professionals, faculty members, undergraduate and postgraduate students of the Department of Chinese Studies, University of Malaya. A total of 138 responses were received with a response rate of 77.5%. The respondents are asked to rate the Chinese studies collection, services and facilities on a 5-point scale. Open-ended questions are provided to allow users to provide comments and suggestions for improvement. The results show that the undergraduates of years 2 and 3 and the postgraduates are less satisfied with the collection and services compared with the undergraduates of year 1, faculty members and library professionals. A gap analysis was also carried out to compare the satisfaction level between the library professionals and the respondents of the Department of Chinese Studies. The results show that there is no significant gap between the performance evaluation by library professionals and library users’ expectations in any particular areas. With the results obtained, the University of Malaya Library may prepare an action plan to address the common areas of discontent and target for improvement. The Library may consider expanding the depth of collection with more up-to-date printed books and journals and to negotiate more budgets for subscription to electronic resources. The Library may also consider adopting the Evans’ model for collection development of the Chinese studies collection.